Proceedings of the 19th Koli Calling International Conference on Computing Education Research 2019
DOI: 10.1145/3364510.3364517
|View full text |Cite
|
Sign up to set email alerts
|

An International Comparison of K-12 Computer Science Education Intended and Enacted Curricula

Abstract: This paper presents an international study of K-12 Computer Science implementation across

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
5

Relationship

4
6

Authors

Journals

citations
Cited by 54 publications
(30 citation statements)
references
References 44 publications
0
30
0
Order By: Relevance
“…In addition the study found the intervention had differing affects on student cohorts clustered by performance (which agrees with the literature [48]). This effect could be compounded, with a new upper second level computer science curriculum in Ireland [40] and internationally [11][12][13], where students may enter the course with formal prior performance, and as it is an optional subject, many students may still be entering the courses with little to no prior experience, creating a larger than seen before divide.…”
Section: Resultsmentioning
confidence: 99%
“…In addition the study found the intervention had differing affects on student cohorts clustered by performance (which agrees with the literature [48]). This effect could be compounded, with a new upper second level computer science curriculum in Ireland [40] and internationally [11][12][13], where students may enter the course with formal prior performance, and as it is an optional subject, many students may still be entering the courses with little to no prior experience, creating a larger than seen before divide.…”
Section: Resultsmentioning
confidence: 99%
“…[60], [61]) and degree accreditation [51], [62]. When establishing a model for viewing computer science education initiatives, it is apparent that there is substantial diversity between education systems -from formal school curricula through to tertiary education, as well as wider education policy and funding -and this can create obstacles when trying to understand progress made in one country and potentially replicate it in another [63], [64]. This is particularly relevant to the devolved (and diverging) educational systems of the UK, as well as the variety of its disparate interventions, especially formal curricula and post-compulsory/tertiary education.…”
Section: Future Work and Replicabilitymentioning
confidence: 99%
“…Only England, Italy and Scotland show a positive CS self-esteem (negative values correspond to a positive CS self-esteem). While further work is required to unpack this finding, the differences could be due to each country's intended and enacted curriculum [19].…”
Section: Countrymentioning
confidence: 99%